Cross-National Comparison of the Association between Adult Child Educational Attainment and Older Parents’ Functional Health - Yulin Yang; Karla Renata Flores Romero; Sirena Gutierrez; Ah-Reum Lee; Emma Nichols; Jacqueline Torres (The Journals of Gerontology, Series A: Biological Sciences and Medical Sciences, 2026)
Abstract Background Mounting evidence points to the protective role of adult child education in older parents' health, including their risk of ADL and IADL difficulties. Yet, little is known whether this association varies cross-nationally due to contextual differences in intergenerational transfers, family dynamics, and other factors. This study examines the relationship between adult child education and parents’ functional health outcomes across countries, using comparable population-based datasets. Methods We used harmonized data from seven population-based studies accessed through the Gateway to Global Aging Data. Our analytic sample included 88,683 adults 60 years and older from 24 countries. We estimated and meta-analyzed associations between adult child education and respondents’ (parents’) difficulty with basic and instrumental activities of daily living (ADL and IADLs), controlling for respondents’ own education and other socio-demographic characteristics. We also considered heterogeneity across parent and child demographics (e.g. parent gender, child gender). Results Across all studies, each additional year of education averaged across adult children was associated with a 3% lower risk of difficulty with both ADLs (95% Confidence Interval [CI]: 0.95, 0.98) and IADLs (95% CI: 0.95, 0.98). Statistical heterogeneity appeared to be driven by one study (e.g. I2 = 78.94% when the study was included vs. I2 = 0.04% when excluded). Results suggest limited heterogeneity across demographic subgroups. Conclusion “Upward” intergenerational benefits of higher adult child education for parents’ late-life ADL and IADL difficulties appear to be relatively consistent across a range of global settings. Further research is needed to uncover the mechanisms driving these cross-national associations.